1972
DOI: 10.1577/1548-8659(1972)101<317:vdtbet>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Damage to Bluegills Exposed to Acutely Toxic Levels of Pesticides

Abstract: Bluegill fingerlings, Lepomis macrochirus, exposed to six different pesticide formulations, developed hemorrhaging and fractures of the caudal vertebrae 4 to 8 hours after treatment. Fish exposed to Dyrene(R) Akton(R), methyl parathion, trichlorfon, phosalone and demeton developed vertebral injury. Injury was observed at concentrations above and below the LC50for each chemical. Disturbance of fish during the early hours of exposure increased mortality and hemorrhage rates. (Use of trade names does not constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1978
1978
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Vertebral anomalies such as kyphosis, lordosis or scoliosis of unknown etiologies have been reported in natural populations of fresh water and marine fish (Bengtsson 1975a;Moore & Hixson 1977). Other investigators have reported vertebral abnormalities, especially scoliosis, occurring in several species of fish as a result of parasitic infections (Hoffman 1962), dietary deficiencies (Halver 1972;Horak 1975), heavy metal exposure (Bengtsson 1975b;Holcombe, Benoit, Leonard & McKim 1976), organochlorine (Meyer 1966;McCann & Jasper The present report describes heretofore undescribed vertebral tissue response of sheepshead minnows during early life and adult exposure to trifluralin. To our knowledge, no pathological response identical to the subsequently described effects has been reported for any animal experimentally exposed to chemicals.…”
Section: Introductionmentioning
confidence: 56%
“…Vertebral anomalies such as kyphosis, lordosis or scoliosis of unknown etiologies have been reported in natural populations of fresh water and marine fish (Bengtsson 1975a;Moore & Hixson 1977). Other investigators have reported vertebral abnormalities, especially scoliosis, occurring in several species of fish as a result of parasitic infections (Hoffman 1962), dietary deficiencies (Halver 1972;Horak 1975), heavy metal exposure (Bengtsson 1975b;Holcombe, Benoit, Leonard & McKim 1976), organochlorine (Meyer 1966;McCann & Jasper The present report describes heretofore undescribed vertebral tissue response of sheepshead minnows during early life and adult exposure to trifluralin. To our knowledge, no pathological response identical to the subsequently described effects has been reported for any animal experimentally exposed to chemicals.…”
Section: Introductionmentioning
confidence: 56%
“…The strong localization of vertebral damage in the posterior backbone area is indicative of the second category of vertebral damage: acute muscular contraction (Spencer, 1967;McCann & Jasper, 1972). Although such contractions may result from electrical shock, we rule out electrofishing as the cause of the deformities in crappies from Lake Decatur.…”
Section: Discussionmentioning
confidence: 97%
“…Although the mechanism for expression is unknown, the abnormalities were attributed to toxicant interference with normal developmental processes, rather than tetany or severe neuromuscular contractions. Sporadic or chronic rigor in skeletal musculature has been proposed as the apparent mechanism for vertebral fractures in studies with older fish exposed to kepone (Couch et al 1977) or organophosphate pesticides (McCann & Jasper 1972, Kumar & Ansari 1984.…”
Section: Discussionmentioning
confidence: 99%